Rice and wheat yield and soil potassium changes in response to potassium management in two soil types - Li, Changzhou; Zhao, Xinlin; Liu, Xiaowei; Lu, Dianjun; Chen, Xiaoqin; Wang, Huoyan; Zhou, Jianmin (Nutrient cycling in agroecosystems, 2020)
The soil non-exchangeable potassium (K) pool contributes significantly to meeting crop K requirements. The objective of this study was to determine wheat and rice grain yield responses to different concentrations of sodium tetraphenylboron (NaTPB) extractable non-exchangeable K in soils. A field experiment was conducted over a period of 4 years using three K application strategies in soils with high (JY) and low (GD) levels of non-exchangeable K. In both soils, rice yield was unaffected by K application during the 4-year study period. However, in GD soil, wheat was unable to produce grains without K additions (0 K) during the fourth wheat season. In JY soil, wheat grain yield decreased only in the 0 K (by 11%) compared with the recommended K application during the fourth wheat season. Different responses in wheat between the two soils indicated that NaTPB-non-exchangeable K better represented the soil K supplying capacity than it did exchangeable K. Lower amounts of non-exchangeable K extracted by NaTPB in GD soil were mainly due to lower amounts extracted during the 0–5 s and 5–10 min time periods. Straw retention alone resulted in negative K balances, with 100 kg K ha −1 yr −1 in JY soil and 95 kg ha −1 yr −1 in GD soil. In conclusion, recommended K application combined with NaTPB-K monitoring would be useful for sustaining crop yield and soil K fertility among different soils in rice–wheat cropping systems.